COMPARATIVE STUDY BETWEEN STAPLER HAEMRRHOIDOPEXY AND OPEN HAEMRRHOIDECTOMY - Dr Chetan Agrawal; Dr Naveen Patidar; Dr Rishikant Vashishtha (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background- Hemorrhoids are one of the most common diseases of mankind, affecting 4%–36% of the general population. Naturally present anal cushions that generate clinical symptoms (expand, bleed, become thrombosed, or prolapse) are referred to as hemorrhoids. Aim- To study the outcome of stapler haemrrhoidopexy versus open haemrrhoidectomy. Methods and materials- This prospectivet study was conducted in the department of General Surgery, Sri Aurobindo Medical College and PGI, Indore, Madhya Pradesh, India over 18 month duration from September 2022 to February 2024. this study comparing Open versus Stapled hemorrhoidopexy for the management of Grade 3 and 4 hemorrhoids. Study was conducted on 80 patients admitted and operated for hemorrhoids at our institute who fulfilled the inclusion and exclusion criteria.Data was collected by using Proforma. The patients were categorized into two study groups (each included 40 patients): group 1 was treated by stapled hemorrhoidopexy, and group 2 had conventional hemorrhoidectomy. Results- Of 80 patients, 57 (71.25%) were males and 23 (28.7%) were females. The maximum number of patients (65%) belonged to the age group 31 to 50 years. The predominant symptom was bleeding per rectum in 65% of cases followed by Something protruding out of the anal canal 50 % of cases. The operating time (p= 0.04) and hospital stay (P=0.0003) were much less in the stapler hemorrhoidectomy group as compared to the open procedure group. Also, postoperative pain (visual analogue scale)(p=0.01) was less in the stapler hemorrhoidectomy group. The stapler group had an early return to normal activities as compared to the open hemorrhoidectomy group(P=0.02). Conclusion- We have concluded that stapled hemorrhoidectomy has good patient compliance, less complications and better outcome. It may be a good choice for treating hemorrhoids of the third and fourth grades. Additional clinical trials are also required to validate our study’s findings. In order to prevent a recurrence, it is also essential that patients receive dietary and lifestyle adjustments in addition to surgical care. It is advised to conduct additional research with a larger patient population and a longer follow-up duration in order to provide more positive findings.